Становлення проектованого Чорнобильського радіаційно-екологічного біосферного заповідника - Попович, Сергій; Popovych, Sergij (Східноєвропейський національний університет імені Лесі Українки, 2016)
Акцентовано увагу на географічній доцільності створення Чорнобильського радіаційно-екологічного біосферного заповідника, стисло описано природні умови, окреслено хронологічні події його становлення, роль ботаніків і зоологів у цьому процесі й місце в транскордонній мережі природно-заповідних територій та еко-мережі різних рівнів. The importance and the current state of knowledge about the problem are pointed in the article. The main attention is focused on geographical sensible of establishing a Biosphere Reserve in the Ukrainian Polissya in general and in the Chornobyl Exclusion Zone in particular. Also, the natural conditions of the area are described briefly. The key periods of the idea formation of establishing a Biosphere Reserve are outlined by applying scientific and historical research methods and analyzing scientific bibliography, reference data and legal documents. History of the Biosphere Reserve is considered in terms of periodization by decades. For each of them highlighted the role of scientists, government and public environmental authorities in this process. The role of botanists and zoologists is especially appreciable. As conclusion, on the basis of the Chornobyl Radiation-Ecological Biosphere Reserve is planned to create Ukrainian-Belarusian Biosphere Reserve, as well as key areas of pan-European, national, regional and local levels of the econet organization.
Formation of Projected Chornobyl Radiation-Ecological Biosphere Reserve
Keywords: Чорнобильська зона; природно-заповідна мережа; історія заповідника; біосферний заповідник; Chornobyl Exclusion Zone; nature-reserved network; the history of the reserve; Biosphere Reserve